Synthesis and characterization of unsupported copper sulfide for mercury trapping in aqueous system / Yap Pei Lay - Yap, Pei Lay (2012)
Two phase pure copper sulfides, rhombohedral phase digenite (Cu9S5) and hexagonal phase covellite (CuS) have been successfully prepared via hydrothermal method using copper nitrate and sodium thiosulfate without any assisting agent. The structural, chemical, and thermal properties of the as-synthesized phase pure systems were investigated with various characterization techniques, including powder X-ray diffraction (PXRD), scanning and transmission electron microscopy (SEM and TEM), BET gas sorption, X-ray fluorescence (XRF), energy dispersive X-ray scpectroscopy (EDX), thermogravimetric analysis coupled to mass scpectroscopy (TGA-MS), as well as differential scanning calorimetry (DSC) methods. In this study, the phase pure covellite has shown a potential ability to remove Hg(II) in aqueous system with maximum sorption capacity of ca. 400 mg/ g can be reached at pH 4. The collected experimental data is best fitted to Langmuir isotherm and the sorption of Hg(II) onto covellite in aqueous system is favored in a wide range of pH. This was supported by the calculated thermodynamic parameter, ΔG° which has shown that the sorption of Hg(II) onto covellite is favorable in a wide range of pH, particularly at low pH. Apart from that, three synthesis parameters (synthesis temperature, Cu: S mole ratio, and synthesis time) have been systematically investigated throughout the study. It was found that synthesis temperature and Cu: S mole ratio determined the phase purity, crystal phase, and morphology of the final products formed; while synthesis time has pronounced effect on the crystallite size of the yields. Furthermore, several mechanistic pathways leading to the final formation of covellite were proposed and discussed based on the detailed analysis of PXRD done at different synthesis temperatures. This current study also revealed that the renowned most stable phase in copper sulfide family, covellite has transformed into a mixed phase of pentahydrate copper sulfate and covellite at ambient condition after a certain period. It could be shown that covellite is an air-sensitive material which undergoes structural changes after exposure to moisture or air. This discovery was supported with various observations from PXRD, EDX, and TG-MS techniques. Therefore, phase stability study was conducted to find out the most efficient way to store copper sulfides besides to investigate the stability of covellite over a series of time at ambient condition. The phase stability experiments indicated that covellite with the common washing and storage methods described in the research methodology was stable up to 4 weeks. Covellite with the purging of nitrogen gas before storage is the best method to prevent covellite from further oxidation.